A multimodal analysis of enactment in everyday interaction in people with aphasia. Issue 12 (2nd December 2019) - Groenewold, Rimke; Armstrong, Elizabeth
ABSTRACT: Background : "Multimodal communication" is a relatively common term in aphasia research. However, the scope of studies on multimodal interaction in aphasia is generally restricted to one or two multimodal resources, and the type of discourse analysed is often not representative of authentic interaction. Finally, the interpersonal (versus referential) functions of multimodal resources are frequently overlooked. Aims : The purpose of this study was to explore the multimodal realisation of enactments by people with aphasia in everyday interaction. Methods & Procedures : Authentic interactions of six people with aphasia interacting with communication partners of their choice were systematically analysed. Frameworks originating from non-brain-damaged studies were applied to examine the characteristics and functions of linguistic, multimodal, and stance-taking resources used to realise enactments. Outcomes & Results : Even though the participants used the same multimodal resources as non-brain-damaged communicators, the frequencies and characteristics were different. The relationship between multimodal resources and interpersonal functions was different as well. Conclusions : People with aphasia use the same multimodal resources as non-brain-damaged communicators, indicating their retained strengths. However, their higher use of intonation, gesture, and – to a lesser extent – facial expression indicates that these may be important "meaning making" resources for them, which could be utilised more in therapeutic endeavours.